Research on the Application, Challenges, and Countermeasures of Artificial Intelligence in English Teaching and Learning - Xue, Wei (Pacific International Journal, 2024)
Artificial intelligence has been applied in various fields and has brought new developments to these areas. In English teaching and learning, artificial intelligence optimizes the allocation of English education resources, breaks down the barriers of time and space, and enables English educators and learners to fully utilize their time to complete teaching and learning tasks. Artificial intelligence is the electronic teaching assistant for English teachers, and it is the electronic teacher and companion for students. Through automation and intelligence, artificial intelligence helps English teachers eliminate a significant amount of effort, giving them more time and energy to dedicate to teaching and increasing the effectiveness of English instruction. By offering individualized learning experiences, artificial intelligence aids students in increasing the effectiveness of their learning. However, artificial intelligence brings some challenges to English teaching and learning, and addressing these challenges can bring greater development to English teaching and learning and even the teaching and learning of other subjects.